A 0.3 THz VCO using gm‐enhanced technology in 55 nm CMOS. Issue 6 (31st March 2022) - Fu, Haipeng; Song, Qi; Ma, Kaixue
Abstract: A power combined terahertz (THz) voltage‐controlled oscillator (VCO) is proposed to increase the output power. Based on the traditional transformer‐feedback structure, a new negative conductance enhanced (gm‐enhanced) technology is presented to enhance the start‐up of the proposed THz VCO by adding additional transistors to offset the loss of the source inductance. In addition, a short transmission line is used as a zero‐phase shifter to lock the three single‐core VCOs for consistent frequency, phase, and amplitude. The fully integrated 300 GHz VCO design is fabricated in 55‐nm complementary metal oxide semiconductor (CMOS) process. The measurement results show that by modulating the bias voltage of the transistors, the VCO can achieve a tuning range of 301.2–304.2 GHz with a maximum output power of −7.5 dBm. The chip area is only 554 μm × 530 μm.